The Impact of Real Estate Investment Trusts (Reits) on Global Real Estate Markets - Liang, Renze (Transactions on Economics, Business and Management Research, 2024)
Real estate investment trusts (REITs) affect global real estate markets, with this research focusing on the complex financial procedures and investment strategies that determine these consequences. This study examines how market capitalization, P/E ratios, and revenue growth affect REIT performance in the US and worldwide. Regression is used to analyze data from FTSE Russell, Nareit, and S&P Global. According to studies, income-seeking investors can first find high dividend yields appealing. However, they can indicate financial concerns, which can lower market performance. The results show that significant revenue growth indicates operational and organizational health and is tied to market performance. Additionally, the article examines the interconnection of global REIT markets, highlighting the huge volatility spillovers and unequal integration of these markets. To mitigate this partial integration, investors should diversify and manage risk. The report also examines how REITs in developed and emerging nations are changing to promote stability, growth, and fundraising. This study concludes that adaptive skills and structural flaws of REITs should be understood to illuminate risk management and investment strategy in the context of global economic instability.